Punishment, cooperation, and cheater detection in 'noisy' social exchange - Gary Bornstein; Ori Weisel (Games, 2010)
Explaining human cooperation in large groups of non-kin is a major challenge to both rational choice theory and the theory of evolution. Recent research suggests that group cooperation can be explained by positing that cooperators can punish non-cooperators or cheaters. The experimental evidence comes from public goods games in which group members are fully informed about the behavior of all others and cheating occurs in full view. We demonstrate that under more realistic information conditions, where cheating is less obvious, punishment is much less effective in enforcing cooperation. Evidently, the explanatory power of punishment is constrained by the visibility of cheating.
Keywords: 330; public-goods game; punishment; cooperation; reciprocity; experimental games